Negative electrode sheet, method for manufacturing the same, and battery
Patent Information
- Application Number
- CN202510884109.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-27
AI Technical Summary
[0004]有鉴于此,本发明致力于提供一种负极极片及其制备方法和电池,以解决现有锂电池中枝晶生长的问题
(1)本发明的负极极片包括集流体和聚合物保护层,其中聚合物保护层包括由刚性链段和柔性链段组成的嵌段聚合物和锂盐。其中,富含锂盐的聚合物层可促进金属锂表面形成大量的Li3N无机界面层,引导均匀和致密的锂金属颗粒沉积,促进固态电解质界面膜保护效果的长期维持,同时聚合物兼具刚性和柔性的保护层,刚性组分可以提高保护层的机械模量,从而抑制枝晶生长,而柔性组分能承受金属锂负极沉积/溶解过程中的界面波动,从而显著提高循环稳定性。此外,丙烯酸酯类化合物中含有大量的醚氧键,能与锂盐中的锂离子进行配位,从而有利于离子传输,同时丙烯酸酯类化合物中含有两个碳碳双键,能够形成稳固的三维交联网络结构,可进一步提高聚合物保护层的机械强度。
Smart Images

Figure SMS_5 
Figure SMS_6 
Figure SMS_11
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, specifically to a negative electrode sheet, its preparation method, and a battery. Background Technology
[0002] Lithium metal anodes have a theoretical specific capacity 10 times higher than graphite (3860 mAh / g) and the lowest electrode potential (-3.04 V), making lithium metal batteries the best choice for next-generation battery systems. However, the high reactivity of lithium metal and the unstable solid electrolyte interface film easily induce rampant dendrite growth and drastic volume changes, ultimately leading to poor lithium deposition / stripping reversibility and potential safety hazards, severely hindering the application of lithium metal batteries.
[0003] A stable lithium metal interface is one of the essential conditions for the practical application of lithium metal batteries, with electrolyte design being the most critical factor. Ether electrolytes exhibit excellent compatibility with lithium metal, and lithium nitrate (LiNO3), a commonly used additive in ether electrolytes, can promote the formation of a Li3N-rich SEI film, significantly improving battery performance. However, as a "sacrificial electrolyte additive," electrochemical performance deteriorates when LiNO3 is depleted. Furthermore, conventional ether electrolytes cannot be used in high-voltage battery systems due to their narrow electrochemical window, and LiNO3 has poor solubility in carbonate-based electrolytes (10⁻¹⁰). -5 The concentration of lithium metal per liter (g / mL) limits the further application of lithium metal batteries. Furthermore, due to the immense volume expansion, the solid electrolyte interphase (SEI) film formed by the reaction of lithium metal and organic electrolyte is extremely prone to breakage during cycling, resulting in continuous consumption of lithium metal and electrolyte, thus reducing the battery's cycle life. Summary of the Invention
[0004] In view of this, the present invention aims to provide a negative electrode sheet, a method for preparing the same, and a battery, in order to solve the problem of dendrite growth in existing lithium batteries.
[0005] To solve the above-mentioned technical problems, this application is implemented as follows: The present invention provides a negative electrode sheet, the negative electrode sheet comprising a current collector and a polymer protective layer disposed on at least one surface of the current collector; The polymer protective layer comprises a block copolymer and a lithium salt; The block copolymer comprises rigid segments and flexible segments; the polymer monomer of the rigid segments comprises cyano-containing acrylamide compounds; and the polymer monomer of the flexible segments comprises acrylate compounds. The lithium ions in the lithium salt and the amide and / or cyano groups in the rigid segment are connected by chemical bonds; the anions in the lithium salt and the imino groups in the rigid segment are connected by hydrogen bonds.
[0006] Optionally, the mass ratio of the polymer monomer of the rigid segment to the polymer monomer of the flexible segment is (0.2~0.8):1, preferably (0.3~0.5):1.
[0007] Optionally, the mass ratio of the lithium salt to the polymer monomer of the rigid chain segment is (0.5~1.5):1, preferably (0.8~1):1.
[0008] Optionally, the lithium salt includes at least one selected from lithium nitrate, rubidium nitrate, lithium difluorophosphate, and lithium tetrafluoroborate; optionally, the cyano-containing acrylamide compound includes... , , and At least one of the following; optionally, the chemical formula of the acrylate compound is shown in formula (1): Equation (1) Where n is an integer from 1 to 10, preferably an integer from 1 to 5; Optionally, the acrylate compound includes at least one of polyethylene glycol diacrylate, ethylene glycol diacrylate, and diethylene glycol diacrylate.
[0009] Optionally, the block copolymer has the structural formula shown in formula (2): Equation (2); Wherein, m1, m2, and m3 are each an integer from 1 to 20, preferably an integer from 5 to 10.
[0010] A second aspect of the present invention also provides a method for preparing a negative electrode sheet, comprising the following steps: S1. A cyano-containing acrylamide compound and a lithium salt are heated and mixed to obtain a deep eutectic solvent; S2. The photoinitiator, acrylate compound and deep eutectic solvent are subjected to a first mixing treatment to obtain a precursor solution; S3. The precursor solution is coated onto at least one side of the current collector and subjected to photocuring polymerization.
[0011] Optionally, the mass ratio of the cyano-containing acrylamide compound to the lithium salt is 1:(0.8~1). The mass ratio of the acrylate compound to the deep eutectic solvent is 1:(4~6); The mass ratio of the photoinitiator to the acrylate compound is (0.01~0.15):1.
[0012] Optionally, the photoinitiator includes at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and benzophenone.
[0013] Optionally, in step S1, the conditions for the heating and mixing treatment include: a temperature of 80~100℃ and a time of 15~30min; Optionally, in step S2, the first mixing treatment is carried out under light-protected conditions; Optionally, in step S3, the conditions for the photocuring polymerization reaction include: a light source including ultraviolet light with a wavelength of 360~410nm and an intensity of 4~8mW / cm². 2 The time is 1 to 5 minutes.
[0014] A third aspect of the present invention also provides a battery comprising a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode sheet described above and / or a negative electrode sheet prepared according to the preparation method described above.
[0015] The beneficial technical effects of the present invention through the above technical solution are as follows: (1) The negative electrode sheet of the present invention includes a current collector and a polymer protective layer, wherein the polymer protective layer includes a block polymer composed of rigid segments and flexible segments and a lithium salt. The lithium salt-rich polymer layer promotes the formation of a large amount of Li3N inorganic interface layer on the surface of lithium metal, guiding the deposition of uniform and dense lithium metal particles and promoting the long-term maintenance of the protective effect of the solid electrolyte interface film. Simultaneously, the polymer provides both rigid and flexible protective layers. The rigid component can increase the mechanical modulus of the protective layer, thereby inhibiting dendrite growth, while the flexible component can withstand interface fluctuations during the deposition / dissolution process of the lithium metal negative electrode, thus significantly improving cycle stability. Furthermore, the acrylate compounds contain a large number of ether oxygen bonds, which can coordinate with lithium ions in the lithium salt, thereby facilitating ion transport. Simultaneously, the acrylate compounds contain two carbon-carbon double bonds, which can form a stable three-dimensional cross-linked network structure, further improving the mechanical strength of the polymer protective layer.
[0016] (2) The method for preparing the negative electrode sheet of the present invention firstly involves the interaction between lithium ions in the lithium salt and amide and cyano groups in the cyano-containing acrylamide compound to form chemical bonds, and the interaction between the anions in the lithium salt and the imino groups in the cyano-containing acrylamide compound to form intermolecular hydrogen bonds, thereby forming a deep eutectic solvent between the lithium salt and the cyano-containing acrylamide compound; under the action of a photoinitiator, the acrylate compound and the deep eutectic solvent undergo cross-linking polymerization to form a polymer protective layer on the surface of the current collector. By utilizing the strong interaction forces in the deep eutectic molecules to introduce lithium salt into the polymer protective layer, the concentration of lithium salt in the system can be maximized, thus the polymer protective layer is rich in lithium salt. The lithium salt stored in the polymer protective layer can be continuously decomposed in carbonate electrolytes and form a large amount of Li3N inorganic interface layer on the surface of metallic lithium, guiding the deposition of uniform and dense lithium metal particles and promoting the long-term maintenance of the protective effect of the solid electrolyte interface film. Acrylic ester compounds contain a large number of ether oxygen bonds, which can coordinate with lithium ions in lithium salts, thus facilitating ion transport. At the same time, acrylic ester compounds contain two carbon-carbon double bonds. Acrylamide compounds containing cyano groups can form a stable three-dimensional cross-linked network structure with acrylic ester compounds. In the three-dimensional cross-linked network structure, the cyano-containing acrylamide compounds are rigid segments, which gives the polymer protective layer mechanical strength and is more conducive to resisting the growth of lithium dendrites. The acrylic ester compounds in the cross-linked structure are flexible segments, which give the protective layer a certain degree of elasticity, allowing the protective layer to adapt to the infinite volume expansion during the cycling process of lithium metal batteries and withstand the interfacial fluctuations during the deposition / dissolution process of lithium metal anodes, thereby significantly improving the cycle stability of the battery.
[0017] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation
[0018] This invention discloses a negative electrode sheet, its preparation method, and a battery. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It is particularly important to note that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0019] In the description of this invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0020] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0021] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0022] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0023] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0024] To address the problem of dendrite growth in lithium batteries in existing technologies, this invention adopts the following technical solution: This invention provides a negative electrode sheet, which includes a current collector and a polymer protective layer disposed on at least one surface of the current collector; The polymer protective layer includes block copolymers and lithium salts; The block copolymer includes rigid segments and flexible segments; the polymer monomers of the rigid segments include cyano-containing acrylamide compounds; the polymer monomers of the flexible segments include acrylate compounds. In lithium salts, lithium ions and amide and / or cyano groups in rigid segments are linked by chemical bonds; in lithium salts, anions and imino groups in rigid segments are linked by hydrogen bonds.
[0025] In this negative electrode, the polymer protective layer being disposed on at least one surface of the current collector means that the polymer protective layer can be disposed on one surface of the current collector along its own thickness direction, or on two surfaces of the current collector along its own thickness direction. Here, "surface" can be the entire area of the current collector or a part of the current collector; the present invention does not have any particular limitation in this regard, as long as the purpose of this application can be achieved.
[0026] The negative electrode of this invention includes a current collector and a polymer protective layer. The polymer protective layer comprises a block polymer composed of rigid and flexible segments and a lithium salt. The lithium salt-rich polymer layer promotes the formation of a large amount of Li3N inorganic interface layer on the lithium metal surface, guiding the deposition of uniform and dense lithium metal particles and promoting the long-term maintenance of the solid electrolyte interface film's protective effect. Simultaneously, the polymer provides both rigidity and flexibility; the rigid component increases the mechanical modulus of the protective layer, thereby suppressing dendrite growth, while the flexible component can withstand interface fluctuations during the deposition / dissolution process of the lithium metal negative electrode, thus significantly improving cycle stability. Furthermore, the acrylate compounds contain a large number of ether oxygen bonds, which can coordinate with lithium ions in the lithium salt, thus facilitating ion transport. The acrylate compounds also contain two carbon-carbon double bonds, which can form a stable three-dimensional cross-linked network structure, further improving the mechanical strength of the polymer protective layer.
[0027] According to the present invention, the mass ratio of rigid-segment polymer monomers to flexible-segment polymer monomers is (0.2~0.8):1. In this invention, a suitable mass ratio of rigid-segment polymer monomers to flexible-segment polymer monomers can both give the block copolymer a certain degree of elasticity, allowing the polymer protective layer to adapt to volume expansion during lithium metal battery cycling and improve cycle stability, and give the block copolymer high mechanical strength, suppressing dendrite growth. As an example, the mass ratio of rigid-segment polymer monomers to flexible-segment polymer monomers can be any value from 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, and 0.8:1, or any value within the range formed by any two of the above values. In this invention, if the content of rigid-segment polymer monomers is too high, it will lead to a decrease in the flexibility of the block polymer, failing to improve the cycle performance of the battery; if the content of flexible-segment polymer monomers is too high, it will lead to a lower mechanical strength of the block copolymer, failing to suppress dendrite growth. Preferably, the mass ratio of the polymer monomer with rigid segments to the polymer monomer with flexible segments is (0.3~0.5):1.
[0028] According to the present invention, the mass ratio of lithium salt to rigid-chain polymer monomer is (0.5~1.5):1. In this invention, a suitable mass ratio of lithium salt to rigid-chain polymer monomer facilitates the formation of a clear and transparent deep eutectic solvent. As an example, the mass ratio of lithium salt to rigid-chain polymer monomer is any value from 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, and 1.5:1, or any value within the range of any pairwise values mentioned above. In this invention, if the lithium salt content is too high, only an opaque sol can be formed; if the rigid-chain polymer monomer content is too high, the protective effect of the formed polymer layer will be weak. Preferably, the mass ratio of lithium salt to rigid-chain polymer monomer is (0.8~1):1.
[0029] Exemplarily, the lithium salt includes at least one selected from lithium nitrate, rubidium nitrate, lithium difluorophosphate, and lithium tetrafluoroborate. Preferably, the lithium salt includes lithium nitrate. In this invention, the nitrate ions in lithium nitrate can promote the formation of a Li3N-rich SEI film.
[0030] For example, cyano-containing acrylamide compounds include , , and At least one of them.
[0031] For example, the chemical formula of acrylate compounds is shown in formula (1): Equation (1) Where n is an integer from 1 to 10. For example, n can be 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10. Preferably, n is an integer from 1 to 5.
[0032] For example, acrylate compounds include at least one of polyethylene glycol diacrylate, polyethylene glycol diacrylate, and diethylene glycol diacrylate.
[0033] For example, the structural formula of the block copolymer is shown in formula (2): Equation (2); Wherein, m1, m2, and m3 are each independently an integer from 1 to 20. For example, m1, m2, and m3 can each be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20. Preferably, m1, m2, and m3 are each independently an integer from 5 to 10.
[0034] A second aspect of the present invention also provides a method for preparing a negative electrode sheet, comprising the following steps: S1. A cyano-containing acrylamide compound and a lithium salt are heated and mixed to obtain a deep eutectic solvent; S2. The photoinitiator, acrylate compound and deep eutectic solvent are mixed in a first process to obtain a precursor solution; S3. The precursor solution is coated on at least one side of the current collector and subjected to photocuring polymerization.
[0035] The method for preparing the negative electrode of the present invention involves firstly, the lithium ions in the lithium salt and the amide and cyano groups in the cyano-containing acrylamide compound interact to form chemical bonds, and the anions in the lithium salt and the imino groups in the cyano-containing acrylamide compound form intermolecular hydrogen bonds, thereby forming a deep eutectic solvent between the lithium salt and the cyano-containing acrylamide compound. Under the action of a photoinitiator, the acrylate compound and the deep eutectic solvent undergo cross-linking polymerization to form a polymer protective layer on the surface of the current collector. The strong interaction forces in the deep eutectic molecules introduce the lithium salt into the polymer protective layer, maximizing the concentration of lithium salt in the system, thus resulting in a lithium-rich polymer protective layer. The lithium salt stored in the polymer protective layer can continuously decompose in carbonate electrolytes and form a large amount of Li3N inorganic interface layer on the surface of metallic lithium, guiding the deposition of uniform and dense lithium metal particles and promoting the long-term maintenance of the protective effect of the solid electrolyte interface film. Acrylic ester compounds contain a large number of ether oxygen bonds, which can coordinate with lithium ions in lithium salts, thus facilitating ion transport. At the same time, acrylic ester compounds contain two carbon-carbon double bonds. Acrylamide compounds containing cyano groups can form a stable three-dimensional cross-linked network structure with acrylic ester compounds. In the three-dimensional cross-linked network structure, the cyano-containing acrylamide compounds are rigid segments, which gives the polymer protective layer mechanical strength and is more conducive to resisting the growth of lithium dendrites. The acrylic ester compounds in the cross-linked structure are flexible segments, which give the protective layer a certain degree of elasticity, allowing the protective layer to adapt to the infinite volume expansion during the cycling process of lithium metal batteries and withstand the interfacial fluctuations during the deposition / dissolution process of lithium metal anodes, thereby significantly improving the cycle stability of the battery.
[0036] As an example, N-cyanomethacrylamide is selected as a cyano-containing acrylamide compound, and lithium carbonate is selected as the lithium salt. The structural formula of the deep eutectic solvent is shown in the following formula (3): Equation (3).
[0037] According to the present invention, the mass ratio of the cyano-containing acrylamide compound to the lithium salt is 1:(0.8~1). In this invention, a suitable mass ratio of the cyano-containing acrylamide compound to the lithium salt contributes to the formation of a clear and transparent deep eutectic solvent. As an example, the mass ratio of the cyano-containing acrylamide compound to the lithium salt can be any value from 1:0.8, 1:0.85, 1:0.9, 1:0.95, and 1:1, or any value within the range of any pairwise values mentioned above. In this invention, if the content of the cyano-containing acrylamide compound is too high, the protective effect of the formed polymer layer will be weak; if the content of the lithium salt is too high, only an opaque sol can be formed.
[0038] According to the present invention, the mass ratio of acrylate compound to deep eutectic solvent is 1:(4~6). In this invention, a suitable mass ratio of acrylate compound to deep eutectic solvent helps to form a polymer protective layer with certain mechanical strength and elasticity. As an example, the mass ratio of acrylate compound to deep eutectic solvent can be any value from 1:4, 1:4.5, 1:5, 1:5.5, and 1:6, or any value within the range of any two of the above values. In this invention, if the content of acrylate compound is too high, the mechanical strength of the polymer protective layer will be weak and insufficient to resist the growth of lithium dendrites; if the content of deep eutectic solvent is too high, the polymer protective layer will be brittle and unable to adapt to volume expansion during cycling.
[0039] According to the present invention, the mass ratio of photoinitiator to acrylate compound is (0.01~0.15):1. As an example, the mass ratio of photoinitiator to acrylate compound can be any value from 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1, and 0.15:1, or any value within the range of any two of the above values.
[0040] For example, the photoinitiator includes at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and benzophenone.
[0041] According to the present invention, in step S1, the conditions for the heating and mixing treatment include: a temperature of 80~100℃ and a time of 15~30min. As an example, in step S1, the conditions for the heating and mixing treatment include: the temperature can be any value from 80℃, 82℃, 85℃, 86℃, 88℃, 90℃, 92℃, 94℃, 95℃, 98℃, and 100℃, or any value within the range of any two of the above values; the time can be any value from 15min, 17min, 20min, 22min, 24min, 25min, 28min, and 30min, or any value within the range of any two of the above values.
[0042] According to the present invention, in step S2, the first mixing process is carried out under light-protected conditions.
[0043] According to the present invention, in step S3, the conditions for the photocuring polymerization reaction are as follows: the light source includes ultraviolet light with a wavelength of 360~410nm and an intensity of 4~8mW / cm. 2 The time is 1-5 minutes. As an example, in step S3, the conditions for the photocuring polymerization reaction are: the light source includes ultraviolet light, with wavelengths of any value from 360nm, 370nm, 380nm, 390nm, 400nm, and 410nm, or any value within the range of any two of these values; the intensity can be 4 mW / cm². 2 5mW / cm 2 6mW / cm 2 7mW / cm 2 and 8mW / cm 2 The time can be any value in the above range or any value within the range of any two of the above values.
[0044] A third aspect of the present invention also provides a battery comprising a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode sheet described above and / or a negative electrode sheet prepared according to the preparation method described above.
[0045] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.
[0046] Example 1 The preparation of the negative electrode sheet includes the following steps: S1. In a glove box, N-cyanomethacrylamide was heated at 80°C for 25 min, and then an equal mass of LiNO3 was added. The mixture was then stirred at room temperature in a magnetic stirrer for 1 h to form a homogeneous solution deep eutectic solvent (DES). S2. In a glove box, polyethylene glycol diacrylate (PEGDA) containing 1% photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP) is added to the DES obtained in S1, and stirred in the dark to form a precursor solution, wherein the mass ratio of PEGDA to DES is 1:4. S3. In a glove box, smooth the surface of the lithium-copper composite strip, pour the precursor solution onto the surface of the lithium-copper composite strip, and use a scraper with a 3μm gap to evenly coat the surface of the lithium-copper composite strip with the precursor solution. Then place it at a wavelength of 365nm and an intensity of 5mW / cm. 2 Irradiate under a UV lamp for 2 minutes to obtain a negative electrode sheet.
[0047] Example 2 The preparation of the negative electrode sheet includes the following steps: S1. In a glove box, N-cyanomethacrylamide is heated at 80°C for 25 min, and then 80% of the mass of N-cyanomethacrylamide in LiNO3 is added. The mixture is then stirred at room temperature in a magnetic stirrer for 1 h to form a homogeneous solution deep eutectic solvent (DES). S2. In a glove box, polyethylene glycol diacrylate (PEGDA) containing 1% photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP) is added to the DES obtained in S1, and stirred in the dark to form a precursor solution, wherein the mass ratio of PEGDA to DES is 1:5. S3. In a glove box, smooth the surface of the lithium-copper composite strip, pour the precursor solution onto the surface of the lithium-copper composite strip, and use a scraper with a 3μm gap to evenly coat the surface of the lithium-copper composite strip with the precursor solution. Then place it at a wavelength of 365nm and an intensity of 5mW / cm. 2 Irradiate under a UV lamp for 2 minutes to obtain a negative electrode sheet.
[0048] Example 3 The preparation of the negative electrode sheet differs from that in Example 1 in that: In step S1, N-cyanomethacrylamide is replaced with .
[0049] Everything else is the same as in Example 1.
[0050] Example 4 The preparation of the negative electrode sheet differs from that in Example 1 in that: In step S1, the mass ratio of N-cyanomethacrylamide to LiNO3 is 1:0.9.
[0051] Everything else is the same as in Example 1.
[0052] Example 5 The preparation of the negative electrode sheet differs from that in Example 1 in that: In step S2, the mass ratio of PEGDA to DES is 1:6.
[0053] Everything else is the same as in Example 1.
[0054] Comparative Example 1 The preparation of the negative electrode sheet differs from that in Example 1 in that: There is no polymer protective layer.
[0055] Everything else is the same as in Example 1.
[0056] Comparative Example 2 The preparation of the negative electrode sheet includes the following steps: S1. Add N-cyanomethacrylamide and polyethylene glycol diacrylate (PEGDA) in a mass ratio of 1:1 to dimethyl sulfoxide (DMSO) solution. The mass ratio of DMSO to PEGDA is 2:1. Stir at 45°C for 1 hour. Then add 1% of the mass of PEGDA as photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP) and stir until homogeneous to form a precursor solution.
[0057] S2. In a glove box, smooth the surface of the lithium-copper composite strip, pour the precursor solution onto the surface of the lithium-copper composite strip, and use a scraper with a 3μm gap to evenly coat the surface of the lithium-copper composite strip with the precursor solution; then place it at a wavelength of 365nm and an intensity of 5mW / cm. 2 Irradiate under a UV lamp for 2 minutes to obtain a lithium metal anode with a polymer protective layer.
[0058] Battery assembly and performance testing 1. Battery assembly Assemble a Li||Li symmetric cell with both electrodes being negative electrode sheets prepared from the various examples and comparative examples, and the electrolyte being 1.2M LiPF6-EC:EMC:FEC (volume ratio 10:10:1).
[0059] 2. Performance Testing The battery is at 1mA / cm 2 Current density and 1mAh / cm 2 Cyclic performance tests were conducted at the areal capacity: first at 1 mA / cm 2 Constant current discharge at current density for 1 hour, followed by discharge at 1 mA / cm². 2 The discharge overpotential of each Li ||Li symmetric cell was recorded as a function of the number of cycles after constant current charging at the current density for 1 hour. The results are shown in Table 1.
[0060] Table 1 As shown in Table 1, the lithium metal battery of the present invention exhibits significantly improved cycle performance, with no significant increase in overpotential after 500 cycles.
[0061] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a current collector and a polymer protective layer disposed on at least one surface of the current collector; The polymer protective layer comprises a block copolymer and a lithium salt; The block copolymer comprises rigid segments and flexible segments; the polymer monomer of the rigid segments comprises cyano-containing acrylamide compounds; and the polymer monomer of the flexible segments comprises acrylate compounds. The lithium ions in the lithium salt and the amide and / or cyano groups in the rigid segment are connected by chemical bonds; the anions in the lithium salt and the imino groups in the rigid segment are connected by hydrogen bonds.
2. The negative electrode sheet according to claim 1, characterized in that, The mass ratio of the polymer monomer of the rigid segment to the polymer monomer of the flexible segment is (0.2~0.8):
1.
3. The negative electrode sheet according to claim 2, characterized in that, The mass ratio of the polymer monomer of the rigid segment to the polymer monomer of the flexible segment is (0.3~0.5):
1.
4. The negative electrode sheet according to claim 1, characterized in that, The mass ratio of the lithium salt to the polymer monomer of the rigid chain segment is (0.5~1.5):
1.
5. The negative electrode sheet according to claim 4, characterized in that, The mass ratio of the lithium salt to the polymer monomer of the rigid chain segment is (0.8~1):
1.
6. The negative electrode sheet according to claim 1, characterized in that, The lithium salt includes at least one of lithium nitrate, lithium difluorophosphate, and lithium tetrafluoroborate. And / or, the cyano-containing acrylamide compounds include , , and At least one of them; And / or, the chemical formula of the acrylate compound is shown in formula (1): Equation (1) Where n is an integer from 1 to 10.
7. The negative electrode sheet according to claim 6, characterized in that, n is an integer from 1 to 5.
8. The negative electrode sheet according to claim 6, characterized in that, The acrylate compounds include at least one of polyethylene glycol diacrylate, ethylene glycol diacrylate, and diethylene glycol diacrylate.
9. The negative electrode sheet according to any one of claims 6 to 8, characterized in that, The structural formula of the block copolymer is shown in formula (2): Equation (2); Where m1, m2, and m3 are each an integer from 1 to 20.
10. The negative electrode sheet according to claim 9, characterized in that, m1, m2, and m3 are each an integer between 5 and 10.
11. A method for preparing a negative electrode sheet according to any one of claims 1 to 10, characterized in that, Includes the following steps: S1. A cyano-containing acrylamide compound and a lithium salt are heated and mixed to obtain a deep eutectic solvent; S2. The photoinitiator, acrylate compound and deep eutectic solvent are subjected to a first mixing treatment to obtain a precursor solution; S3. The precursor solution is coated onto at least one side of the current collector and subjected to photocuring polymerization.
12. The method for preparing the negative electrode sheet according to claim 11, characterized in that, The mass ratio of the cyano-containing acrylamide compound to the lithium salt is 1:(0.8~1). The mass ratio of the acrylate compound to the deep eutectic solvent is 1:(4~6); The mass ratio of the photoinitiator to the acrylate compound is (0.01~0.15):
1.
13. The method for preparing the negative electrode sheet according to claim 11, characterized in that, The photoinitiator includes at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and benzophenone.
14. The method for preparing the negative electrode sheet according to claim 11, characterized in that, In step S1, the conditions for the heating and mixing treatment include: a temperature of 80~100℃ and a time of 15~30 min; and / or, In step S2, the first mixing process is performed under light-protected conditions; and / or, In step S3, the conditions for the photocuring polymerization reaction are as follows: the light source includes ultraviolet light with a wavelength of 360~410nm and an intensity of 4~8mW / cm. 2 The time is 1 to 5 minutes.
15. A battery, characterized in that, The battery includes a negative electrode sheet, wherein the negative electrode sheet includes the negative electrode sheet according to any one of claims 1 to 10 and / or the negative electrode sheet prepared by the preparation method according to any one of claims 11 to 14.
Citation Information
Patent Citations
Methacrylate-based polymer electrolyte as well as preparation method and application thereof
CN117013064A
Bipolar artificial SEI (solid electrolyte interface) membrane for lithium metal negative electrode as well as preparation method and application of bipolar artificial SEI membrane
CN117175035A